2021
DOI: 10.1130/ges02309.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the tectono-sedimentary evolution of the Early–Middle Jurassic Tlaxiaco Basin in southern Mexico: New insights into the crustal attenuation history of southern North America during Pangea breakup

Abstract: During Pangea breakup, several Jurassic extensional to transtensional basins were developed all around the world. The boundaries of these basins are major structures that accommodated continental extension during Jurassic time. Therefore, reconstructing the geometry of Jurassic basins is a key factor in identifying the major faults that produced continental attenuation during Pangea breakup. We reconstruct the tectono-sedimentary evolution of the Jurassic Tlaxiaco Basin in southern Mexico using sedimentologic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Several of those faults imply a complex history of WNW-ESE displacements during the thinning of the lithosphere caused by the Pangea breakup. Such processes, and the existence of that fault system, was previously envisaged by several authors (e.g., Anderson and Schmidt, 1983;Pindell and Kennan, 2009) and recently documented in southern Mexico by Zepeda-Martínez et al (2021), who concluded that southern Mexico migrated from a more westward position during the Jurassic, toward ESE thanks to the action of such fault system (Figure 12). In this model it is envisaged that at least some of the magmatic arc previously emplaced into the continental crust, including LUP, suffered the same displacement toward ESE.…”
Section: Tectonic Implicationsmentioning
confidence: 60%
See 2 more Smart Citations
“…Several of those faults imply a complex history of WNW-ESE displacements during the thinning of the lithosphere caused by the Pangea breakup. Such processes, and the existence of that fault system, was previously envisaged by several authors (e.g., Anderson and Schmidt, 1983;Pindell and Kennan, 2009) and recently documented in southern Mexico by Zepeda-Martínez et al (2021), who concluded that southern Mexico migrated from a more westward position during the Jurassic, toward ESE thanks to the action of such fault system (Figure 12). In this model it is envisaged that at least some of the magmatic arc previously emplaced into the continental crust, including LUP, suffered the same displacement toward ESE.…”
Section: Tectonic Implicationsmentioning
confidence: 60%
“…While the obtained ages sit the LUP magmatism in the Middle Jurassic, two regimes contributed to the generation of this magmatism for this time span: 1) the magmatism related to the subduction of the Farallon and Cocos plates, which were active at least since the beginning of Mesozoic, as the widespread magmatism since the Early Jurassic testifies (e.g., Spikings et al, 2015;Martini and Ortega-Gutiérrez, 2018, and Figure 12); together with 2) the extensional processes that produced several rift basins associated to the onset of the Gulf of Mexico opening (e.g., Engebretson et al, 1985;Pindell and Kennan, 2009;Martini and Ortega-Gutiérrez, 2018;Parolari et al, 2022, and references therein), the breakup of Pangea (e.g., Martini et al, 2022) with the relative migration of Gondwana toward SE and the formation of several NS and WNW-oriented lateral faults in southern Mexico (#1 to 5 in Figure 12, see also Zepeda-Martínez et al, 2021). The NS-trending lateral faults are subparallel to the Tamaulipas-Chiapas Transform zone, which corresponds to the main trace of the Yucatán displacement during the opening of the Gulf of Mexico (Figure 12).…”
Section: Tectonic Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Cualac Formation is composed of conglomerates, fine-conglomeratic sandstone, and thin shale strata (Zepeda-Martínez, et al, 2021). Ten lithofacies have been recognized that are organized into two different architectural elements, Gravel Bars and Bedforms (GB) and Floodplain fines (FF), which according to Zepeda-Martínez et al ( 2021) was part of a coalescent alluvial fan system.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…13). Evidence of sinistral block motion along the Mexican continental margin during at least Early and Middle Jurassic time is provided by the occurrence of kilometre-scale, WNW-trending, brittle to brittle-ductile leftlateral faults, which controlled the architecture and evolution of major transtensional basins in southern Mexico (Martiny et al 2012;Zepeda-Martínez et al 2021). Therefore, these major left-lateral faults may be interpreted as the inboard expression of the Trans-America-transform boundary along the Mexican continental margin.…”
Section: Tectonic Modelmentioning
confidence: 99%